The Influence of Customer Service and Product Diversification on Customer Loyalty - Lu'lu Ul Maknunah; Hanik Amaria (LPPM Institut Bisnis dan Informatika Kesatuan, 2025)
This study investigates the influence of customer service and product diversification on customer loyalty. The research addresses the question of how service quality and diversification strategies jointly shape loyalty in the Indonesian business context, where competition and evolving customer expectations demand both operational excellence and product innovation. Using a quantitative explanatory approach, data were collected from 377 customers through a structured online survey. The measurement model demonstrated strong reliability and validity, with all constructs meeting psychometric standards. Structural equation modeling with partial least squares revealed that customer service (β = 0.390, p < 0.001) and product diversification (β = 0.354, p < 0.001) both exert positive and significant effects on customer loyalty. The R² value of 0.467 indicates that these two variables explain nearly half of the variance in loyalty. The study discusses these findings by linking them to established theories, including SERVQUAL, the Ansoff matrix, and the commitment-trust theory. Results highlight that while customer service has a slightly stronger influence, the synergy of service and product strategies is crucial for sustaining loyalty. These findings provide theoretical contributions to loyalty research and practical insights for firms operating in emerging markets.